2016
DOI: 10.1063/1.4964788
|View full text |Cite
|
Sign up to set email alerts
|

Three-dimensional topographies of water surface dimples formed by superhydrophobic water strider legs

Abstract: The supporting forces of all the legs have been simultaneously measured through a natural phenomenon inspired shadow method, by capturing water strider leg shadows to calculate the expelled water volume and the equivalent floating forces according to Archimedes' principle, with a sensitivity up to nN~pN/pixel. The method was verified by comparing to electronic balance to weight water striders. The supporting force acted on legs was found to linearly proportional to its shadow area, which geometry clearly indic… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(16 citation statements)
references
References 53 publications
0
16
0
Order By: Relevance
“…Atomic-Like Motion of Oil Drops. When a small amount of carbon tetrachloride (CCl 4 ) liquid dyed with a biological stain was dropped on the surface of an ethanol and DI water mixture (the drops float at the air−liquid interface which is mainly because of surface tension and buoyancy 17,18 ), we found that the CCl 4 liquid forms lens shaped drops at the air−liquid interface. In general, the dropped liquid can spread out or form a drop, and its behavior depends on the spreading parameter.…”
Section: Resultsmentioning
confidence: 99%
“…Atomic-Like Motion of Oil Drops. When a small amount of carbon tetrachloride (CCl 4 ) liquid dyed with a biological stain was dropped on the surface of an ethanol and DI water mixture (the drops float at the air−liquid interface which is mainly because of surface tension and buoyancy 17,18 ), we found that the CCl 4 liquid forms lens shaped drops at the air−liquid interface. In general, the dropped liquid can spread out or form a drop, and its behavior depends on the spreading parameter.…”
Section: Resultsmentioning
confidence: 99%
“…When the density of the plate is smaller than that of the solution, the plate can float at the air–liquid interface. However, for a plate with a larger density than that of the liquid, due to buoyancy and surface tension, the plate can also float on the surface without sinking . Hence, a plate with a larger density than that of the liquid solution also can be transported and controlled by our method.…”
Section: Methodsmentioning
confidence: 99%
“…However, for a plate with a larger density than that of the liquid, due to buoyancy and surface tension, 14 the plate can also float on the surface without sinking. 15 Hence, a plate with a larger density than that of the liquid solution also can be transported and controlled by our method. The liquid marble is a type of liquid drop stabilized by solid powders at the surface.…”
Section: ■ Experimental Sectionmentioning
confidence: 99%
“…Yeh's groups adopted Xanthosoma sagittifolium leaves with a WCA of 146° as templates to prepare a superhydrophobic surface showing a WCA of 153° on a cold‐rolled steel substrate using nanocasting techniques. [ 49,50 ] In addition, Chen et al [ 51 ] fabricated a superhydrophobic surface through the solvothermal method and self‐assembly functionalization. Resembling the lotus leaf, the fabricated superhydrophobic surface possesses hierarchical micro/nano structures.…”
Section: Superhydrophobic Surfacesmentioning
confidence: 99%